Identifying candidate markers associated with the early progression of Alzheimer’s disease pathology in APPPS1-21 mouse model - Bani Younes, Ghada (fi=Turun yliopisto|en=University of Turku|, 2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease manifested clinically as memory loss in the early stages of the disease and cognitive dysfunction at later stages. These symptoms can be due to synaptic dysfunction and neuronal loss, respectively. The main histopathological features associated with the disease are the accumulation of beta amyloid and neurofibrillary tangles, the two findings that have been suspected to be related to the cause of AD symptoms. Alzheimer’s disease which has been discovered more than one hundred years ago, still has no cure or therapeutic agents that can halt its progression. To help develop options to prevent the progression of the disease, early markers need to be identified. Recently, extracellular matrix proteins were suggested to play a role in the pathogenesis of AD. In this project, a group of extracellular matrix proteins, namely chondroitin sulfate proteoglycans (CSPG), were studied for the first time in young APPPS1-21 AD mouse model and compared to wild type mouse model of the same age (2 months) using WFA lectin. Coronal brain slices of wild type mouse (n=3) and APPPS1-21 transgenic mouse (n=3) were compared in different brain regions using staining technique. The number of cells surrounded by CSPG proteins were higher in the hippocampus and lower in the cortex of the transgenic mice compared to wild type mice, however, the difference was not statistically significant. Further investigation in a larger number of animals is needed to study the early changes in CSPGs in APPPS1-21 mouse model.